Supporting schools during the implementation of the health-promoting school approach: The roles of a healthy school advisor - Bartelink, Nina; van Dongen, Bonnie; Kremers, Stef; Renders, Carry; van Vlokhoven, Boukje; van Koperen, Marije; van Assema, Patricia (Frontiers in Public Health, 2022)
Introduction The health-promoting school (HPS) approach was developed by the World Health Organization to create health promotion changes in the whole school system. Implementing the approach can be challenging for schools because schools are dynamic organizations with each a unique context. Many countries worldwide have a health promotion system in place in which healthy school (HS) advisors support schools in the process of implementing the HPS approach. Even though these HS advisors can take on various roles to provide support in an adaptive and context-oriented manner, these roles have not yet been described. The current study aims to identify and describe the key roles of the HS advisor when supporting schools during the dynamic process of implementing the HPS approach. Methods The study was part of a project in which a capacity-building module was developed for and with HS advisors in the Netherlands. In the current study, a co-creation process enabled by participatory research was used in which researchers, HS advisors, national representatives, and coordinators of the Dutch HS program participated. Co-creation processes took place between October 2020 and November 2021 and consisted of four phases: (1) a narrative review of the literature, (2) interviews, (3) focus groups, and (4) a final check. Results Five roles were identified. The role of “navigator” as a more central one and four other roles: “linking pin,” “expert in the field,” “critical friend,” and “ambassador of the HPS approach.” The (final) description of the five roles was recognizable for the HS advisors that participated in the study, and they indicated that it provided a comprehensive overview of the work of an HS advisor in the Netherlands. Discussion The roles can provide guidance to all Dutch HS advisors and the regional public health organizations that employ them on what is needed to provide sufficient and context-oriented support to schools. These roles can inspire and guide people from other countries to adapt the roles to their own national context.